An In Vitro Bovine Cellular Model for Human Schlemm's Canal Endothelial Cells and Their Response to TGFβ Treatment - Cai, Jingwen (Transl Vis Sci Technol, 2020)
PURPOSE: Due to the limited availability of primary human Schlemm's canal (SC) endothelial cells, we aimed to develop an in vitro cellular model using the angular aqueous plexus (AAP) cells from bovine eyes. METHODS: We harvested a mixture of cells from the trabecular meshwork region including AAP loops from multiple donors, followed by puromycin treatment and immunostaining of Von Willebrand factor and vascular endothelial (VE)-cadherin to confirm identity. Previously identified differentially expressed genes in glaucomatous SC cells were examined in non-glaucomatous SC cells (n = 3) under 0% or 15% equibiaxial strain for 24 hours using droplet digital polymerase chain reaction (ddPCR) and analyzed using the Ingenuity Pathway Analysis (IPA) software application to identify upstream regulators. To compare the cellular responses to candidate regulators of these mechanoresponsive genes, AAP and human SC cells (n = 3) were treated with 5 or 10 ng/mL transforming growth factor beta-2 (TGFβ2) for 24 or 48 hours, followed with expression profiling using real-time PCR or ddPCR. RESULTS: We found that the isolated AAP cells displayed uniform cobblestone-like morphology and positive expression of two endothelial markers. In stretched SC cells, nine glaucoma-related genes were upregulated, and IPA implicated TGFβ as a potential upstream regulator. The effects of TGFβ2 treatment were similar for both AAP and SC cells in a dose- and time-dependent manner, activating TGFBR1 and SMAD2, inhibiting BMP4, and altering expression of three glaucoma-related genes (DCN, EZR, and CYP1B1). CONCLUSIONS: Bovine AAP cells may serve as an alternative cellular model of human SC cells. TRANSLATIONAL RELEVANCE: These AAP cells may be used to study the functional pathways related to the outflow facility.